ANALYSIS OF NETWORK MONITORING SYSTEM USING NETFLOW & SFLOW WITH SILK, NFDUMP, AND NPROBE AS FLOW COLLECTOR - Saputra, Rizky
Computer networks is the fundamental infrastructure needed for a computer system to connect and communicate with each other. Therefore, if something happens that disturbs the performance of a computer network, the performance of the system will be hampered. This thing will cause bad impact, both in terms of technical and financial. One of the best ways to anticipate disruptions in computer networks from both external and internal attacks (such as down network devices), we can use a Network Monitoring System.